The mechanism of maintaining intracellular homeostasis in the red alga Pyropia haitanensis under hyposaline stress - Wen, Jian; Xu, Kai; Ji, Dehua; Xu, Yan; Chen, Changsheng; Wang, Wenlei; Xie, Chaotian (Frontiers in Marine Science, 2022)
The cultivation of hyposaline-tolerant varieties of the red alga Pyropia haitanensis is not only conducive to expanding the area of intertidal seaweed cultivation, but also contributes to preventing eutrophication of coastal waters. Research on the mechanism of hyposaline tolerance of P. haitanensis is an important prerequisite for breeding hyposaline-tolerant varieties. Here, we used proteomics and targeted metabolomics technologies to identify the key proteins and metabolites in thalli of P. haitanensis that changed under two hyposaline stress treatments: 0‰, LSS 0; 5‰, LSS 5. Responses of thalli of P. haitanensis to hyposaline stress included to inhibit protein synthesis, recruit molecular chaperones, and enhance the removal of misfolded proteins to maintain the dynamic balance of protein folding and removal; the response was similar under hypersaline stress. Glycolysis was the main energy supply pathway, and thalli actively maintained the stability of the cell membrane under hyposaline stress, which was distinct from the response to hypersaline stress. Compared with the LSS 0 treatment, P. haitanensis exhibited a more adequate energy supply, more stable endoplasmic reticulum environment and more intact membrane system under the LSS 5 treatment. The results improve understanding of the hyposaline tolerance mechanism of intertidal seaweed and provide a theoretical basis for the development of hyposaline-tolerant varieties.